Digital user behaviour of academicians in a conflict zone, Kashmir. Issue 2 (2014) - Sumeer Gul; Tariq Ahmad Shah; Suhail Ahmad
<x xml:space="preserve"> Abstract </x> Purpose – The aim of this paper is to explore digital user behaviour of academicians in Kashmir (Indian Administered) in the times of conflict (2008‐2010) and peace (2011‐2012). It is an attempt to investigate the influence of political conditions on the usage of electronic resources. Design/methodology/approach – Transaction logs in the form of COUNTER reports from Project MUSE database that represent usage at University of Kashmir, were mined for five years – January 2008 to December 2012. The data was divided in to two time periods; conflict period – 2008 to 2010 and peace period – 2011 to 2012. Findings – There is a strong relationship between peace, conflict and e‐resource usage. The results confirm peace and conflict as explanatory factors on the use of electronic resources in conflict zones, like Kashmir. Research limitations/implications – Understanding how users behave in the online academic environments, the academic administrators can help to satisfy the perceptions and needs of users associated with the electronic resource settings. Practical implications – The study shows that more attention should be given to prevail peace in conflict zones in order to maximise the use of e‐resources. Originality/value – The study is the first of its kind as it is trying to relate the user behaviour with political setups in a conflict zone, Kashmir.